Treatment of gingival recession: Comparative study between subepithelial connective tissue graft and guided tissue regeneration - Rosetti, Elizabeth Pimentel [UNESP]; Marcantonio, Rosemary Adriana Chierici [UNESP]; Rossa Júnior, Carlos [UNESP]; Chaves, Eros S.; Goissis, Gilberto; Marcantonio Júnior, Elcio [UNESP] (Wiley, 2000)
Background: Various procedures have been proposed to treat gingival recession, but few studies compare these procedures to each other. The purpose of this study was to evaluate a clinical comparison of subepithelial connective tissue graft (SCTG) and guided tissue regeneration (GTR) with a collagen membrane in the treatment of gingival recessions in humans. Methods: Twenty-four defects were treated in 12 patients who presented canine or pre-molar Miller Class I and/or II bilateral gingival recessions. Both treatments were performed in all patients, and clinical measurements were obtained at baseline and 18 months after surgery. These clinical measurements included gingival recession height (GR), root coverage (RC), probing depth (PD), keratinized tissue width (KT), and final esthetic result. Results: Both SCTG and GTR with a bioabsorbable membrane and bone graft demonstrated significant clinical and esthetic improvement for gingival recession coverage. The SCTG group was statistically significantly better than GTR for height of GR (SCTG = 0.2 mm, GTR = 1.12 mm, P = 0.02) and KT (SCTG = 4.58 mm, GTR = 2.5 mm, P <0.0001). However, PD was statistically significantly better for GTR than SCTG treatment (GTR = 1.66 mm, SCTG = 1.00, P = 0.01). The 2 procedures were statistically similar in root coverage (SCTG = 95.6%, GTR = 84.2%, P = 0.073). The esthetic condition after both treatments was satisfactory (P = 0.024). Conclusions: It was concluded that the gingival recessions treated with the SCTG group were superior for GR, RC, and KT clinical parameters, while GTR demonstrated better PD reduction. The final esthetic results were similar using both techniques.
Keywords: Barrier; Bioabsorbable; Comparison studies; Connective tissue; Connective tissue/surgery; Gingival recession/surgery; Gingival recession/therapy; Grafts; Guided tissue regeneration; Membranes; collagen; adult; artificial membrane; biodegradable implant; clinical trial; comparative study; connective tissue; controlled clinical trial; controlled study; dental care; female; gingiva; gingiva disease; human; male; methodology; middle aged; oral surgery; patient satisfaction; periodontics; plastic surgery; randomized controlled trial; transplantation; treatment outcome; Absorbable Implants; Adult; Collagen; Connective Tissue; Esthetics, Dental; Female; Gingiva; Gingival Recession; Guided Tissue Regeneration, Periodontal; Humans; Male; Membranes, Artificial; Middle Aged; Oral Surgical Procedures; Patient Satisfaction; Surgical Flaps; Treatment Outcome